Instilling Language Ethics: Strategies for Developing Polite Habits in Elementary Schools - Nurul Lativah; Erma Nurmiati; Dwi Laksminawati; Herlina Setyaningrum; Genne Tiyan; Ovanuari N; Aditya Hermansyah; Reza Dwi K (JELCre - Journal of Education and Learning Creativity, 2025)
This study aims to describe the implementation of the habituation of polite language use as an effort to shape students’ character at SDN Sendang 1, Donorojo District, Pacitan Regency. The study focuses on the role of teachers in cultivating the use of polite language and its influence on the development of students’ character, particularly in appreciating achievement and social care. This research employed a descriptive qualitative approach involving fifth-grade students, classroom teachers, and the school principal as research subjects. Data were collected through observation, interviews, and documentation, while data accuracy was ensured through research technique and source triangulation. Data analysis was conducted using descriptive qualitative methods through the stages of data reduction, data presentation, and conclusion drawing. The results indicate that the habituation of polite language use at SDN Sendang 1 has been implemented consistently through teachers’ role modeling, both in learning activities and in daily interactions within the school environment. This habituation contributes significantly to the development of the character of appreciating achievement, as reflected in students’ mutual respect and appreciation, as well as the character of social care, which is evident in the use of polite, empathetic, and respectful language. However, students’ initiative in demonstrating spontaneous social care still needs to be enhanced through continuous habituation. This study concludes that the habituation of polite language use is an effective strategy in character education and should be strengthened through synergistic collaboration among schools, teachers, and parents so that values of politeness can be optimally internalized within students.